The power of clock time or the time of the people? Latin American politics in the 21st century - Ortega, Jaime (Journal Studies of Public Policy, 2022)
The evaluations of the political events of the last two decades have shed some light on the current ambiguous situation of some Latin American countries. On the one hand, despite its multiple differences, there has been a deployment of a sovereigntist option focused on state reconstruction. While on the other hand, there are pressures and fluctuations imposed by the global market. This article addresses the most significant demarcation lines of three moments: the social resistance to neoliberalism, the initial occupation of the state by progressive forces, and the return of positions that were considered banished from the common sense of the society. Lastly, a brief comment is made on the persistence in the search for relative autonomy in the process of global capitalist’s renewal. The Latin American conjecture seems to demonstrate that time belongs to the people, but clock time belongs to the power.